Knowledge, Attitude and Practices of Medical and Dental Practitioners Regarding COVID 19 Pandemic - Tajwar Jafar, Taimur Hassan Shah, Hani Javaid Mir, Asma Shakoor, Hira Butt, Muhammad Nasir Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the knowledge, attitude and practices of medical and dental practitioners regarding COVID-19. Methodology: A cross sectional study was conducted in College of Dentistry, Sharif Medical and Dental College, Lahore from July 2021 to July 2022 on medical and dental practitioners. Medical and dental practitioners irrespective of their age, gender and specialty of practice were included in the study. Participants who refused to give consent to be included in the study were excluded. Informed consent was taken from the participants before data collection. Data was collected using a pre-validated questionnaire Results: There was a statistically significant difference in the scores of attitude (p=≤0.001) and practices (p=≤0.001) while the non-significant difference in the scores of knowledge (p=0.200) across medical and dental practitioners regarding COVID-19 pandemic. Conclusion: The level of knowledge, attitude and practices of dental practitioners was higher in comparison to the medical practitioners. Keywords: COVID 19 pandemic, Dental practitioners, medical practitioners, knowledge, attitude, practice